#ChristianCheck: TikTok and the Construction of Generation Z Faith - Hamm, Margaret (Journal of religion, media and digital culture, 2023)
This paper examines the media practices of young Christians as expressed in the TikTok trend “#ChristianCheck,” a challenge in which TikTokers create videos displaying objects that represent their faith. Through #ChristianCheck, Christian TikTokers emphasize the tangibility of their faith at a time when United States media expresses anxiety over the “dilution” of Christianity in a new generation of non-religious teens to whom the tangible components of religion do not seem to matter. Ultimately, in the face of notions that Christianity is “dead” or “uncool,” Generation Z TikTokers pose their own understandings of Christianity through reiterative processes oriented around race- and gender-based values.